Rethinking stakeholder participation in strategic planning processes: a case of Zimbabwe’s Colleges of Education - Bhebhe, Gladwin (Midlands State University, 2019)
This study investigated stakeholder participation in strategic planning processes in three teacher training colleges in Zimbabwe. The study was conducted within the qualitative research methodology. Three colleges of education were purposively sampled. All principals in the sampled sites took part in the study. Two Heads of Departments (HODs), two Lecturers in Charge (LICs) two Students Representative Council (SRC) members as well as College Advisory Council Board Members (CACBM) participated in this study. A total of 18 informants participated through interviews. Documents such as strategic planning minutes were scrutinized. Strategic planning meetings were also observed at two sites. The findings were that the practice of strategic planning still appears to be rigid and bureaucratic for organizations that operate in rapidly changing environments such as those in Zimbabwe. Secondly, participation in strategic planning is not all inclusive; only a select few individuals do take part in the planning exercise. Colleges of education and the Ministry focus on the product activities, that is, crafting the strategic plan. They seem to ignore the process activities such as reviewing plans periodically and taking note of key performance indicators which promote continuous improvement. The study also found that participants received no formal training in strategic planning and that the planning process was skewed towards control and compliance; and exhibited managerial accountability tendencies which lie within central bureaucratic approaches. The study recommends that the Ministry of Higher and Tertiary Education and the Department of Teacher Education, at the University of Zimbabwe, in consultation with relevant stakeholders should develop norms and standards for teacher education to align Zimbabwe’s stakeholder participation in strategic planning to the global trends. Colleges should supplement their understanding of operational contexts by exploring possible future trends and circumstances. The criteria for reviewing strategic plans should be developed by peers, and practitioners in the field, in consultation with national norms and standards for teacher education.